Antibacterial activities of plant extract Cinnamomum zeylanicum bark against multidrug-resistant bacteria - Nishteman Mohammad; Shilan Saleem; Rand Balata; Dian Salih (University of Mosul, 2022)
Background : Due to the increased occurrence of bacterial resistance to multiple antimicrobial drugs, there is a constant search for novel therapeutic strategies; medicinal plants represent an important source for obtaining such substances. The antimicrobial activity of extracts and essential oils of medicinal plants has been proven in several studies conducted in countries with diverse flora. Aim : To evaluate the antibacterial activity of cinnamon against multidrug- resistant bacteria. Material and Method: Bacterial susceptibility testing was conducted by the diffusion method on Mueller-Hinton agar using paper discs impregnated with test substances. Results: All test strains were sensitive to the essential oil of cinnamon. We observed low synergistic potential between essential oils against the strain of S. aureus. Conclusion: The essential oil of cinnamon has antibacterial activity against both Gram-positive and Gram-negative strains. Future research should be conducted to define the best concentration and better extraction solution for mastic and cinnamon peels.